1987
DOI: 10.1002/1097-4679(198701)43:1<17::aid-jclp2270430104>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Etiological factors in the development of PTSD in clinical samples of Vietnam combat veterans

Abstract: This paper presents a review of empirical literature that deals with etiological factors in combat‐related post‐traumatic stress disorder (PTSD). Variables implicated in PTSD from three time frames, premilitary, military, and postmilitary, are identified, and findings from relevant research are discussed. There is consistency across studies in showing significant correlations between PTSD and combat exposure and post‐military psychosocial adjustment. Less consistent are the finding with regard to relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 9 publications
3
29
0
Order By: Relevance
“…Hocking (16), for example, concluded that "predispositions" have no determinative role in the linkage between extreme stress and later well-being. Consistent with Hocking's position, studies of Vietnam veterans have found that premilitary factors do not predict PTSD summary scores when combat exposure and military adjustment are controlled (17)(18)(19).…”
mentioning
confidence: 70%
“…Hocking (16), for example, concluded that "predispositions" have no determinative role in the linkage between extreme stress and later well-being. Consistent with Hocking's position, studies of Vietnam veterans have found that premilitary factors do not predict PTSD summary scores when combat exposure and military adjustment are controlled (17)(18)(19).…”
mentioning
confidence: 70%
“…This result supported findings with Vietnam veterans (Foy, Carroll, & Donahue, 1987). There were no demographic differences between the two groups in terms of premigration factors.…”
Section: Discussionmentioning
confidence: 99%
“…By examining individuals who have had similar traumatic histories, the study was better able to identify some factors associated with the development of PTSD among Southeast Asians. Furthermore, to increase comparability with previous PTSD research (see Foy, Carroll, & Donahue, 1987), all events were assessed with reference to three time frames involving premigration, migration, and postmigration periods. The role of anger reactions was also examined in view of previous findings from the veteran-based PTSD research.…”
mentioning
confidence: 99%
“…Cite this article as: Phillips, A.C., Carroll, D., Gale, C.R., Post-traumatic stress disorder (PTSD) is another psychiatric diagnosis which has received much attention with regard to the stress of war exposure (Foy et al, 1987). Individuals with such a diagnosis have also been shown to exhibit alterations in HPA axis hormones, for example, lower cortisol levels have been observed in several studies of patients with PTSD (Yehuda et al, 1990(Yehuda et al, , 1995Mason et al, 2001).…”
mentioning
confidence: 99%